Unidirectional antenna using two-probe excited circular ring above square reflector for polarization diversity with high isolation - Vongsack, S.; Phongcharoenpanich, C.; Kosulvit, S.; Hamamoto, K.; Wakabayashi, T. (My University, 2012)
This paper presents a circular ring antenna fed by two perpendicular probes, both of which are placed above the square re°ector. The antenna is employed to radiate unidirectional beam for polarization diversity reception. A linear isolator is added to improve the isolation between the two probes. The antenna is proposed for the point-to-point communication of Wireless Local Area Network (WLAN) system according to the IEEE 802.11a standard in which the allocated frequency band ranges from 5.150 GHz to 5.825 GHz. The proposed antenna is compact and suitable for mass production. Without the dielectric material, the antenna is free of dielectric loss and capable of high power handling. The prototype antenna was fabricated and measured to verify the theoretical predictions. At the center frequency, the unidirectional pattern with the measured half-power beamwidths in two principal planes of 65 and 75 degrees is achieved. The front-to-back ratio is 31 dB, and the antenna gain is 7.42 dBi. The |S11| and |S21| are respectively -23:09 dB and -33:99 dB; the obtained bandwidth is 23.64%. Based on the aforementioned characteristics, the antenna is a potential candidate for polarization diversity of WLAN applications.